Foreignization and Domestication Strategies in The Bilingual Profile Book of ‘Big Farmer’ - Purnamasari, Yessy; Zewitra; Febryanto, Mohammad; Bakhti, Krisna Yudha (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2025)
This study examines the application of foreignization and domestication strategies in translating the bilingual profile book of POKDARWIS ‘Big Farmer,’ a community-based tourism organization of Desa Kertawangi, West Bandung, Indonesia. Utilizing Venuti’s translation framework (1995), this research identifies how the two strategies are employed to present Culture-Specific Items (CSI) as categorized by Espindola (2005) to both Indonesian and English-speaking audiences, enhancing cross-cultural understanding and promoting tourism. Through qualitative analysis, the findings reveal a tendency of foreignization strategy to preserve cultural uniqueness and a minor amount of domestication to ensure clarity and readability for international readers. The study highlights the importance of adapting cultural terms and region-specific references to maintain both authenticity and accessibility in translation. This research contributes to the broader discussion on translation practices in tourism and cross-cultural communication, suggesting that a mixed approach allows for effective cultural representation while accommodating the target audience’s familiarity. The results have implications for translation studies, especially in bilingual materials for community-based tourism.